Building An Ideal Society From An Islamic Perspective - Hidayat, Rahmat; Uliyah, Taqwatul; Fauzi, Machfud; Solimin, Solimin; Mislawaty, Sri Eva (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
The development and existence of Islam until now with its existence is one of the struggles and da'wah movements that always initiate its delivery to the people and nature. Da'wah has started since the time of the Prophet Muhammad Saw until now, with many upheavals and struggles in grounding Islam through da'wah. There are many verses of Allah Swt that discuss da'wah, such as QS. Ali Imran; 104, 110, QS. An Nahl; 125 and many others similar to the phrase da'wah. If we look back at the preaching struggle of Rosulullah Saw while in Mecca, it is essential to try to invite and call the Quraysh to leave the ignorance of their lives to the way of Allah Swt. So that the main pointer of the content of the Prophet's preaching is human servitude to the Oneness of Allah Swt (tauhid). The core of the first da'wah that must be conveyed is about monotheism to Allah Swt and as the foundation of the movement of human dignity. In various ways and efforts, the Prophet's da'wah both in Mecca and Medina had different characteristics of distributing Islamic information. Departing from the understanding of culture, culture, and wisdom of the community that made the Prophet determine different methods in delivering his da'wah. The development of the people, especially the first to instil monotheism to the people, and the second to build a system of society in sharia. Such is the Islamic civilisation from the way of da'wah as Islam that we know today from the Prophet Muhammad Saw struggling to expand his da'wah departing from Mecca and Medina. So that the Prophet's mission of da'wah is to strengthen the internalisation of the ummah and develop relationships with outside the ummah. This means that this is how the teachings of Islam brought by Rosulullah Saw so that it can build an exclusive and moderate da'wah paradigm. And the Prophet Muhammad's da'wah at that time was the main reference for the life of Islamic society in the midst of diverse and complex streams. As well as the foundation of the struggle and movement of da'wah how da'wah should live and last in the midst of a pluralistic society with its heterogeneity.